Productivity and profitability of vegetable pea (Pisum sativum) under sprinkler irrigation and PSB seed inoculation - SINGH, GURVINDER; CHANDRA, SUBHASH; DASS, ANCHAL (The Indian Journal of Agricultural Sciences, 2026)
Field experiments were conducted during winter seasons of 2007-08 and 2008-09 at Norman E Borloug Crop Research Centre, Pantnagar on sandy loam soil to assess the impact of seed inoculation with phosphate solubilizing bacteria (PSB) and irrigation schedules with sprinklers on vegetable pea (Pisum sativum L.). Results revealed that yield attributes and green pod yield was not influenced significantly by PSB inoculation while irrigation schedules did. Irrigation scheduled at IW: CPE 1.0 through sprinklers produced at par green pod yield with flood irrigation at vegetative and flowering stages but recorded 19.2 and 30.9% higher green pod yield than 0.8 and 0.6 irrigation schedules. Similarly, values of yield components were also higher under this treatment. PSB inoculated treatment recorded 11.1% higher water-use efficiency than no inoculation. Among the irrigation schedules, maximum WUE was noticed with IW: CPE 0.6 treatment (97.0 kg/ ha-cm) while lowest (51.3 kg/ha-cm) was observed with flood irrigation at vegetative and flowering stages. In terms of gross, net return and B: C ratio, IW: CPE 1.0 was superior to other treatments.